On the distribution and history of Saami verbal derivatives in -š- - Kuokkala Juha; Koponen Eino (Tartu Ulikool Kirjastus,Tartu University Press, 2025)
The article presents a comparative-historical survey on Saami verbal derivatives with a suffixal *-š- (or *-šš-), based on extensive dictionary data from all Saami languages. The derivatives are divided into several subtypes using structural and functional criteria, and the distribution of each subtype as well as shared derivatives between Saami languages are investigated in order to illuminate the background of each subtype and their interrelations. It is argued that the essive verbs in *-āše̮- (South Saami vealkasjidh ‘appear white’) and denominal verbs in *-uše̮- (North Saami jallošit ‘play the fool’) as well as the diverse *-(e̮)še̮- verbs in the more peripheral languages descend from a single Proto-Saami *-še̮- derivative suffix with a general verbalizer function. The model of this type has probably also contributed to the emergence of the weak-grade *-Všše̮- type, which mainly consists of borrowings adapted from Finnic *-icce- verbs, such as North Saami dárbbašit (~ Finnish tarvitse-) ‘need’.
Kokkuvõte. Juha Kuokkala, Eino Koponen: Saami -š-verbituletiste esinemisest ja ajaloost. Artiklis esitatakse võrdlev-ajalooline uurimus saami *-š- või *-šš- sufiksiga verbituletistest. Uurimus põhineb laialdasel sõnaraamatuainestikul kõigist saami keeltest. Tuletised jaotatakse strukturaalsete ja funktionaalsete kriteeriumide järgi alltüüpideks, ning iga alltüübi esinemist ja mitmele keelele ühiseid tuletisi vaadeldakse alltüupide tausta ja nende suhete selgitamiseks. Selle põhjal järeldame, et essiivsete *-āše̮ -verbide (lõunasaami vealkasjidh ‘paistma valgena’) ja denominaalsete *-še̮ -verbide (põhjasaami jallošit ‘veiderdama’) ning perifeersemate keelte erinevate funktsioonidega *-(e̮)še̮ -verbide taust peitub ühes ühises algsaami *-še̮-tuletusliites, mis algselt kandnud üldse verbistaja ja frekventatiivsufiksi funktsioone. Selle tüübi eeskuju on tõenäoliselt mõjutanud ka nõrgaastmelise *-Všše̮-tüübi tekkimist, mis peamiselt koosneb läänemeresoome *-icce-verbidest mugandatud laenudest, nagu põhjasaami dárbbašit (~ soome tarvitse-) ‘vajama’.